1971
DOI: 10.1111/j.1600-0765.1971.tb00581.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Determination of immunologlobuline (IgG, IgA and IgM) and identification of IgA‐type in the gingival fluid.

Abstract: Quantitative immunoglobulin determinations were performed by a single radial imrmmo‐diffusion method with verified specificity and precision. The identification of sernm‐IgA or secretory‐IgA in gingival fluid was carried out in double diffusion in gel experiments with the use of a specific anti‐serum to “secretory piece”. Gingival fluid was collected with micropipettes by capillarity from subjects with different degrees of gingival inflammation. Blood and mixed saliva were sampled from each individual at the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

1974
1974
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(36 citation statements)
references
References 25 publications
4
32
0
Order By: Relevance
“…It has been reported earlier that the concentrations of immunoglobulins in the gingival fluid is similar to that of plasma (Holmberg & Killander 1971). Our observations support this result (Table 1).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It has been reported earlier that the concentrations of immunoglobulins in the gingival fluid is similar to that of plasma (Holmberg & Killander 1971). Our observations support this result (Table 1).…”
Section: Discussionsupporting
confidence: 92%
“…It has been held that the electrophorectic pattern obtained from gingival fluid is similar to that of serum (Cimasoni 1974, Brandtzaeg 1975, While due attention has been paid to the immunoglobulins and complement (Holmberg & Killander 1971, Shillitoe & Lehner 1972, the information about other proteins is still scanty. In a recent work, however, a major protein fraction of the gingival fluid and serum from patients with advanced periodontitis was studied (Schenkein & Genco 1977a).…”
Section: Introductionmentioning
confidence: 99%
“…The protein concentrations used for pellicle formation were approximately half the values reported for plasma but of the same magnitude as seen in the literature for gingival crevicular fluid under normal conditions (albumin 20–25 mg/ml, fibrinogen 1–2 mg/ml, fibronectin ?0.1 mg/ml) (28, 29, 36). The concentration of IgA and IgG is reported to be of the same magnitude in plasma and the gingival crevicular fluid; 1.5 and 10 mg/ml, respectively (14, 20). Thus, the protein concentrations used for coating in no case exceeded the concentrations found in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…A number of previous studies have reported that serum proteins, including those studied in the present investigation, are present in the gingival fiuid in varying amounts (Shillitoe & Lehner 1972, Toffefsen & Saltvedt 1980, Brantzaeg 1965, Holmberg & Killander 1971. However, the reported findings in the literature show that the relative concentration of IgG to IgA in the gingival fiuid is 8:1, and that the concentration of albumin and IgG are comparable (Brantzaeg 1965).…”
Section: Discussionmentioning
confidence: 45%